WHAT DO WE KNOW ABOUT CUSTOMER SATISFACTION IN THE HOSPITALITY AND TOURISM INDUSTRY? THE GLIMPSE FROM A BIBLIOMETRIC ANALYSIS - Nuril Aulia Munawaroh; Imam Mukhlis; Arief Noviarakhman Zagladi (Transpublika Publisher, 2024)
Numerous previous studies have emphasized that investigating customer behavior in hospitality and tourism services is a crucial research area that significantly impacts the industry's success, particularly in terms of customer satisfaction. According to a report by Small Business Chron, customer satisfaction holds paramount importance in the hospitality and tourism industry, where customers pay close attention to the quality of service they receive. The goal of this paper is to offer researchers a systematic view of how this topic contributes to the development of effective research channels for future analysis and research on the subject. The method used is bibliometric analysis, and mapping analysis has been conducted involving 107 articles from the SCOPUS database on customer satisfaction spanning from the year 2013 to 2023. The study employs bibliometric analysis of literature using Vosviewer. The findings reveal that research on customer satisfaction has steadily grown over the study period in the hospitality and tourism industry. The network analysis of customer satisfaction publications indicates that important themes covered include service quality, customer experience, customer value, and customer reviews